Interstock-induced anatomical and metabolomic shifts enhance growth and stress adaptation in citrus cultivars - Sugiyatno, Agus; Devy, Nirmala Friyanti; Hardiyanto; Triwiratno, Anang; Widyaningsih, Sri; Budiyati, Emi; Yulianti, Farida; Ashari, Hasim; Dwiastuti, Mutia Erti; Parhusip, Dorkas; Ikarini, Imro’ah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Citrus growers are challenged to be able to produce high yields while being resilient to environmental stress, while maintaining high yield and cultivar potential. However, the use of pummelo as an interstock-despite its growing relevance for cultivar replacement-remains poorly studied in terms of its anatomical and metabolic effects on scion varieties. This study evaluates the impact of Pummelo interstock on the growth, leaf anatomy, and metabolomic profile of three citrus cultivars: Sweet Orange (Manis Pacitan), Tangerine (Siam Pontianak), and Mandarin (Keprok Batu 55). Morphological assessment showed that interstock application increased leaf thickness by 3.9% and palisade layer thickness by 15.2%, with additional adaptations in epidermal and glandular structures suggesting enhanced stress tolerance. Stomatal density rose by 22% in certain combinations. GC-MS metabolomic profiling identified 91 metabolites, with interstock treatments increasing the accumulation of stress-related compounds such as flavonoids and terpenes. Stress-metabolite upregulation reached 59.6% in Keprok Batu 55, 36.2% in Manis Pacitan, and 47.8% in Siam Pontianak. Key pathway modifications involved the stimulation of fatty acid metabolism and the development of glycosylphosphatidylinositol (GPI) anchors in interstocked plants, which led to better morphological and physiological features. These findings highlight the role of interstock technology in promoting vegetative vigor, metabolic reprogramming, and stress adaptation in citrus, with practical implications for improving productivity and sustainability in citrus cultivation. Further research should explore long-term performance and underlying genetic mechanisms.